Factors determining the persistence of prenatal stress urinary incontinence 12 months postpartum - Shuenn-Dhy Chang; Wu-Chiao Hsieh; Sherry Yueh-Hsia Chiu; Kai-Lyn Ng; Ching-Chung Liang (Elsevier, 2023)
Objective: Whilst many studies have explored the mechanisms of stress urinary incontinence (SUI) following various modes of delivery, few have examined outcomes of postpartum SUI in women who experienced new-onset SUI during their pregnancy. Our primary objective was to investigate the risk factors for persistent postpartum SUI in women with new-onset SUI during pregnancy at 1-year follow-up following vaginal delivery. Materials and methods: 303 women with new-onset SUI during pregnancy who underwent vaginal delivery in a university hospital between 2014 and 2015 were included. In-person interviews were conducted for all participants on the second postpartum day, followed by phone interviews at 12 months postpartum, with completion of structured questionnaires, including Urogenital Distress Inventory Short Form (UDI-6) and Incontinence Impact Questionnaire Short Form (IIQ-7). Demographic, obstetrics and questionnaire scores were analyzed and compared between the group of women who experienced persistent postpartum SUI and the group who did not. Results: At 12 months postpartum, 16.5% (n = 50) of women had persistent postpartum SUI, with 83.5% (n = 253) experiencing resolution of SUI symptoms. Maternal age ≥35 years (aOR = 2.62; 95% CI, 1.40-4.87, P = 0.002), gestational age at birth ≥40 weeks (aOR = 2.21; 95% CI, 1.12-4.37, P = 0.022), and severe perineal lacerations (aOR = 2.32; 95% CI, 1.27-4.45, P = 0.013) were independent risk factors for persistent postpartum SUI for women following vaginal delivery at 1-year follow-up. Conclusion: The prevalence of persistent postpartum SUI at 1-year following vaginal delivery is 16.5%, with advanced maternal age, gestational age at birth ≥40 weeks and severe perineal lacerations being independent risk factors.